Molecular Chaperones and Cold Adaptation of Organisms - Gulevsky, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2003)
The review on the problem state of stress proteins: molecular chaperones in the light of their possible role in cold adaptation processes, is presented. Brief history of this question study is adduced. Possible directions for molecular chaperone future investigations are estimated.